Analysis of the PD-1 Ligands Among Gastrointestinal Cancer Patients: Focus on Cancer Immunity - Dai, Lin; Huang, Zilin; Li, Wang (Frontiers in Oncology, 2021)
Many types of gastrointestinal cancer have shown promising outcomes after checkpoint blockade immunotherapy, however it remains largely unclear about programmed death 1 (PD-1) ligands’ expression profiles (CD274 and PDCD1LG2) in the context of human pan-cancer. This work comprehensively analyzed the expression pattern of the PD-1 ligands and the clinical significance in prognosis prediction among 7 types of gastrointestinal malignancies collected from The Cancer Genome Atlas (TCGA) and the Cancer Cell Line Encyclopedia (CCLE) databases. Furthermore, the correlation of CD274/PDCD1LG2 with cancer immunity was also explored. Liver hepatocellular carcinoma (LIHC) patients receiving cytokine-induced killer (CIK) cell immunotherapy at our cancer center were enrolled. The CD274 and PDCD1LG2 displayed inconsistent gene expression levels among diverse cancer cell lines. Typically, abnormal expression level of the CD274 and PDCD1LG2 were detected in both esophageal carcinoma (ESCA) and stomach adenocarcinoma (STAD), where PDCD1LG2 was related to the overall survival for patients in ESCA (P= 0.015) and STAD (P= 0.025). High serum CD274 and PDCD1LG2 levels predicted worse survival in LIHC patients receiving CIK therapy. More importantly, the CD274 and PDCD1LG2 expression levels were significantly correlated with the degrees of Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data (ESTIMATE). In addition, we found that, the CD274 and PDCD1LG2 were correlated with gene markers in tumor-infiltrating immune cells. Furthermore, expression of the CD274 and PDCD1LG2 were correlated with tumor mutation burden (TMB), microsatellite instability (MSI), mismatch repair (MMR), and DNA methyltransferase (DNMT) of different types of cancers. The present work comprehensively analyzed the RNA sequencing of the PD-1 ligands across seven distinct types of gastrointestinal cancers, which provided clues for further studies in cancer immunity and development.